Analisis Laporan Keuangan Pada PT. Bank BNI (Persero) Tbk - Setiawan, Andi (Jurnal Riset Akuntansi, 2021)
A bank is a business entity or financial institution that greatly influences the economy of a country. The purpose of this research is to analyze the financial performance of PT. Bank BNI (Persero) Tbk in 2017-2019 using the CAMEL method. Financial health assessment of PT. Bank BNI (Persero) Tbk is carried out by assessing the aspects of Capital (Capital), Asset Quality, Management (Management), Earning (Rentability), Liquidity (liquidity) which is referred to as CAMEL. The results of the assessment show that the level of financial health of PT. Bank BNI (Persero) Tbk for 3 years for the period 2017-2019 was included in the healthy category with a CAMEL value of 90.2 in 2017, 90.4 in 2018 and 89.7 in 2019.